Peran Rasio Likuiditas, Profitabilitas dan Leverage Dalam Mempengaruhi Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Iin Syofia Y; Deky Hamdani (Magister Ilmu Akuntansi Universitas Jambi, 2023)
High company value shows good company performance. This research was conducted to determine the effect of Liquidity Ratio, Profitability Ratio and Leverage Ratio In Affecting Firm Value. The sample in this research is Manufacturing Companies on the Indonesia Stock Exchange (IDX) during the research period (2017-2021). The number of samples in this study were 5 companies using purposive sampling technique. This study uses multiple linear regression analysis, tests the hypothesis using the T-test to test the regression coefficients partially and the F-test to test the effect simultaneously with a significant level of 5%. The results showed that the variables Liquidity (CR) and Profitability (ROA) had no significant effect on Firm Value (PBV). While the Leverage variable (DER) has a significant influence on Firm Value (PBV)